RETRACTED: Model of the management system of a higher educational institution - Kudryavtseva Irina; Pocebneva Irina; Deniskina Antonina; Narezhnaya Tamara (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001